Lack of effect of aprepitant on digoxin pharmacokinetics in healthy subjects - Feuring, Martin; Lee, Yih; Orlowski, Laura H.; Michiels, Nicole; De Smet, Marina; Majumdar, Anup K.; Petty, Kevin J.; Goldberg, Michael R.; Murphy, M. Gail; Gottesdiener, Keith M.; Hesney, Michael; Brackett, L. Ellen; et al. (Journal of clinical pharmacology, 2003)
Aprepitant is a highly selective neurokinin-1 receptor antagonist that, in combination with a corticosteroid and a 5-hydroxytryptamine3 (5HT3) receptor antagonist, has been shown to be efficacious in the prevention of highly emetogenic chemotherapy-induced nausea and vomiting. In vitro data suggest that aprepitant is a substrate and a weak inhibitor of P-glycoprotein. Thus, the effect of aprepitant on the pharmacokinetics of digoxin, a P-glycoprotein substrate, was examined in a double-blind, placebo-controlled, randomized, two-period crossover study in 12 healthy subjects. Each subject received daily oral doses of digoxin 0.25 mg on Days 1 through 13 during both treatment periods. Aprepitant 125 mg (or matching placebo) was coadministered orally with digoxin on Day 7, and aprepitant 80 mg (or matching placebo) was coadministered orally with digoxin on Days 8 to 11. Aprepitant did not affect the pharmacokinetics of digoxin. The geometric mean ratios (90% confidence interval [CI]) for plasma AUC0-24 h of digoxin (with/without aprepitant) were 0.99 (0.91, 1.09) and 0.93 (0.83, 1.05) on Days 7 and 11, respectively, and the geometric mean ratios (90% CI) for the 24-hour urinary excretion of immunoreactive digoxin (with/without aprepitant) were 0.91 (0.80, 1.04) and 1.00 (0.91, 1.09) on Days 7 and 11, respectively. Thus, aprepitant, when dosed as a 5-day regimen, did not interact with a known substrate of the P-glycoprotein transporter.